Analysis of carbon reinforced lightweight concrete structures and possible applications - LEVIN, RASMUS; NYLUND, LENNART (My University, 2023)
Steel-reinforced concrete has made intricate constructions feasible for more than the past hundred years. There are many benefits of using this effective composite although the service life is challenged by reinforcement corrosion. For applications where a low dead weight is necessary, lightweight concrete (LWC) has become an alternative to normalweight concrete (NWC). However, the drawbacks to LWC are that it is vulnerable for reinforcement corrosion and have a low tensile strength compared to NWC. Still, there is a potential way forward to create lightweight structures that are simultaneously resistant to corrosion. To explore this alternative further, new reinforcement materials must be investigated, e.g. carbon fibre reinforcement (CFR). The material has advantages due to the corrosion resistance of the carbon reinforcement, but carbon bundles and cords have problems with low bond strength between the carbon reinforcement and the concrete, as well as interfilament slip in the reinforcement. Currently, there is a large gap in research regarding the pros and cons of CFR and understanding of how CFR can be optimized using different methods. This study is an attempt to close that gap and provide some answers. To gain knowledge of the behaviour of the reinforcement and the interaction with the concrete, pull-out and four-point bending tests with carbon fibre reinforcement in straight bundles and braided cords have been carried out prior to this thesis. The data from the pull-out experiments were analysed and the data that were deemed characteristic were used as input to a bond stress versus slip model applied in the FE-program DIANA. This bond-slip model was used in FE-analyses of the fourpoint bending tests, and the results were compared to the experimental results. Finally, the bond-slip model was used in analyses of stocky columns, where the carbon reinforcement was used to provide lateral confinement. The analyses of the tests proved that the CFR had a low bond strength to the LWC and that only a few percent of the strength and stiffness of the materials was utilised. The analyses gave a good resemblance to the experimental results, thus they gave a good estimation of the behaviour of the composite. The knowledge gained was further used to discuss suitable applications, e.g. floating pontoons, sewage culverts and edge beams used for bridges. This study attempted to fill the gaps in research regarding CFR in LWC. In the future, more research within this field will be pivotal to further broaden the scope of potential applications and evaluate both advantages and disadvantages.
Keywords: Keywords: Carbon fibre reinforcement, CFR, Lightweight concrete, LWC, Bond slip, Interfilament slip, Pull-out test, Four-point bending test, FE-model